2019
DOI: 10.3390/cancers11060793
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Mutations in miRNA Genes in Lung Cancer—Potential Functional Consequences of Non-Coding Sequence Variants

Abstract: A growing body of evidence indicates that miRNAs may either drive or suppress oncogenesis. However, little is known about somatic mutations in miRNA genes. To determine the frequency and potential consequences of miRNA gene mutations, we analyzed whole exome sequencing datasets of 569 lung adenocarcinoma (LUAD) and 597 lung squamous cell carcinoma (LUSC) samples generated in The Cancer Genome Atlas (TCGA) project. Altogether, we identified 1091 somatic sequence variants affecting 522 different miRNA genes and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 134 publications
(119 reference statements)
4
34
0
Order By: Relevance
“…We also confirmed the recurrence of mutations in hsa-miR-21 as previously identified with the Annotative Database of miRNA Elements (ADmiRe) 48 . Not surprisingly, the current results overlap almost perfectly with our earlier results obtained for LUAD and LUSC 31 . Minor discrepancies result from some differences in the technical approach (see Materials and Methods).…”
Section: Significantly Overmutated Mirna Genessupporting
confidence: 92%
See 4 more Smart Citations
“…We also confirmed the recurrence of mutations in hsa-miR-21 as previously identified with the Annotative Database of miRNA Elements (ADmiRe) 48 . Not surprisingly, the current results overlap almost perfectly with our earlier results obtained for LUAD and LUSC 31 . Minor discrepancies result from some differences in the technical approach (see Materials and Methods).…”
Section: Significantly Overmutated Mirna Genessupporting
confidence: 92%
“…An additional indication of miRNA gene sensitivity to genetic alteration is their general high conservation and the decreased density of common SNPs in miRNA hairpin sequences [28][29][30] , which resembles the commonly known phenomenon of the decreased level of nonsynonymous SNPs in protein-coding sequences. In our recent analysis of somatic mutations in lung cancers, we confirmed that seed mutations affect the vast majority of the predicted targets and showed that mutations in miRNA genes often alter the predicted structure of miRNA precursors 31 . miRNAs in cancers were also considered in the context of somatic mutations found in mRNAs that affect mRNA-miRNA and competing endogenous RNA (ceRNA)-miRNA interactions 32,33 .…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations